An examination of the migratory transition of elite young European soccer players to the English Premier League - Richardson, D.; Littlewood, M.; Nesti, M.; Benstead, L. (Journal of Sports Sciences, 2012)
The migration of soccer players has increased in recent years. In this study, we examined the experiences of elite young soccer players as they engaged in a migratory transition from their home country to an English Premier League (EPL) club. Five young players, who made the migratory transition between the ages of 16 and 24, were interviewed. Data were analysed using the principles of content analysis. Verbatim text was then aligned to the emergent themes. Results indicate that young migratory players face the initial frenzy that is associated with an approach from an EPL club before going through a "decision" phase, followed by a period of "migration" and "acculturation" before establishing (or not) their "home from home". The challenges of leaving home and family while trying to establish themselves as a professional player in an environment that (still) appears to be beset with (traditional) English soccer culture (i.e. high tempo, ruthless, macho, and aggressive) are recounted. While the player's family was a significant source of social support, there is still a need for qualified personnel (e.g. sports psychologists) and/or appropriately trained international recruitment staff and football agents (i.e. in areas of social, psychological, and/or performance lifestyle) to support young players through their migratory transition.